Two Pre-Islamic Places of Worship in the Tourism Landscape of the UAE - De Man, Adriaan (Religions, 2022)
As suggested by the title, this paper explores two of the several archaeological sites that configure religious loci in the territory of the current United Arab Emirates. It does so by assessing their relevance, by refining their nature and historical context, and by analyzing their positioning as components of a tourism mix. The core research question is whether or not integration is accomplished. Both structures are quite well known in the academic literature and underwent excavation and conservation investments that allow their proper use and promotion. Discussion and conclusions identify challenges for achieving an appropriate integration with conditioning supply factors.